Newly synthesized poly(glycidyl methacrylate-co-3-thienylmethylmethacrylate)-based electrode designs for phenol biosensors - Ozoner, Seyda Korkut; Erhan, Elif; Yilmaz, Faruk; Celik, Asuman; Keskinler, Bülent (Elsevier, 2010)
A newly synthesized poly(glycidyl methacrylate-co-3-thienylmethylmethacrylate) [poly(GMA-co-MTM)] was designed to fabricate various HRP electrodes for detection of phenol derivatives. The results showed that the poly(GMA-co-MTM)/polypyrrole composite film microarchitecture provided a good electroactivity as a result of pyrrole and thiophene interaction, and provided chemical bonds for enzyme immobilization via the epoxy groups of poly(GMA-co-MTM). The glassy carbon-based working electrode displayed significantly higher performance for the same composite film configuration comparing to the gold-based working electrode. Poly(GMA-co-MTM)/polypyrrole/HRP coated glassy carbon electrode exhibited a fast response less than 3s, a high sensitivity (200 nA mu M for hydroquinone), a good operational stability (%RSD values ranged between 2 and 5.1 for all phenolics). a long-term stability (retained about 80% of initial activity at the end of 40th day) and a low detection limit ranging between 0.13 and 1.87 mu M for the tested. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Phenol biosensor; Horseradish peroxidase; Poly(glycidyl methacrylate-co-3-thienylmethylmethacrylate); Polypyrrole; Thiophene